2021
DOI: 10.5114/pq.2021.105885
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of head posture muscles’ viscoelastic parameters on pulmonary and functional capacity in healthy individuals

Abstract: IntroductionForward head posture (FHP) is known to have a large influence on respiratory function by weakening the respiratory muscles. This cross-sectional study is designed to examine the relationship between the tonus, stiffness, and elasticity of head posture muscles and pulmonary capacity.MethodsOverall, 16 FHP and 17 non-forward head posture (NFHP) individuals were evaluated. The tonus, stiffness, and elasticity of the upper trapezius, semispinalis capitis, pectoral muscles, and sternocleidomastoid muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several studies reported a significant influence of FHP on respiratory function, determined by a general weakening of the accessory respiratory muscles [7][8][9]. The FHP role in respiratory function was found to be more pronounced in patients already suffering from chronic respiratory diseases [10], with a reduction of forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1) and the activity of the accessory muscles of respiration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a significant influence of FHP on respiratory function, determined by a general weakening of the accessory respiratory muscles [7][8][9]. The FHP role in respiratory function was found to be more pronounced in patients already suffering from chronic respiratory diseases [10], with a reduction of forced vital capacity (FVC), forced expiratory volume in 1 s (FEV1) and the activity of the accessory muscles of respiration [11].…”
Section: Introductionmentioning
confidence: 99%